Cluster Analysis Consumer by Marketing Factors Buying Decision of Battery Electric Vehicles - Tangjaturasopon, Ajcharapan (Journal of Management Sciences Suratthani Rajabhat University, 2025)
Nowadays, battery electric vehicles are gaining more and more attention from the public, as evidenced by sales and the number of electric cars running on the roads. This research aims to study personal data, purchase decision behavior, marketing mix factors, and consumer classification of those interested in battery electric vehicles. A purposive sampling method was used with questionnaires distributed to a sample of 400 people. Descriptive statistical analysis including percentage, frequency, mean, and standard deviation, and cluster analysis were considered in this research using hierarchical cluster techniques. The results found that the majority of the sample were single women aged under 35 years. They held a bachelor's degree, had an average income between 15,001–25,000 baht, and worked as government officers or state enterprise employees. They drove battery electric vehicles approximately 21–50 kilometers per day and decided to purchase a sedan car with a budget of 400,000–800,000 baht. They made decisions by themselves with consideration of price and value for money. They used online media, the Internet, and social media channels to obtain information about battery electric vehicles to support their decisions. Marketing mix factors affected the decision to purchase battery electric vehicles. Consumer classification can be divided into four types: Group 1: Consumer group that emphasizes value for money; Group 2: Consumer group that focuses on marketing activities; Group 3: Consumer group that focuses on product quality; and Group 4: Consumer group that focuses on value for money and marketing activities. The research results can be used as guidelines for determining marketing activities that are appropriate for consumer groups, and can also be used in production planning to develop products to meet the needs of diverse consumers.